Assessing CREMAs' Capacity to Govern Landscape Resources in the Western Wildlife Corridor of Northern Ghana. - Bayala, Eric Rega Christophe; Zida, Mathurin; Asubonteng, Kwabena Owusu; Ros-Tonen, Mirjam A. F.; Reed, James; Siangulube, Freddie Sayi; Ickowitz, Amy; Djoudi, Houria; Sunderland, Terry (Environmental Management, 2025)
Ghana initiated community resource management areas (CREMAs) as a community-based natural management approach to give local communities the right and power to manage natural resources within their territorial boundaries. The expectation is that communities and their environment would prosper through more equitable landscape governance and sustainable use of natural resources. However, the challenges to achieving full functionality of CREMA and expected results, particularly in the Western Wildlife Corridor in northern Ghana, raise questions about the governance actors' capacity. Therefore, this study aims to assess the capacity of actors to take ownership of and lead the governance processes implied by the CREMA approach. Based on focus group discussions and individual interviews, we found that the capacities of the CREMA governance bodies are weak to implement the CREMA approach effectively. The lack of knowledge and technical skills to support multi-actor processes, the weak collaboration between actors, and the lack of sustainable financial inflows and livelihood support are key challenges to be addressed for better CREMA performance. Despite these constraints, local actors' enthusiasm and willingness to engage more actively in the governance of their landscape constitute an opportunity for an improved implementation of the CREMA approach. We suggest that initiatives to strengthen the technical and financial capacities of governance bodies and raise awareness among the local population are necessary to improve the functioning and performance of CREMAs. In addition, actions to improve the livelihoods of local communities will enhance the mobilization and engagement of social groups in the implementation of the CREMA concept.